Comparative ab initio studies on morphology and stability of the C/BN and SiC/GaN heterostructure interfaces. (12th April 2017) - Sznajder, M; Hrushka, N; Grabowski, M; Majewski, J A
Abstract: The morphology, charge distribution, and stability of interfaces in the diamond/c-BN and 3C-SiC/zb-GaN heteropolar junctions grown along the [1 1 1] and [0 0 1] crystallographic directions are obtained from first principles calculations in the framework of density functional theory. It is shown that reconstructions occurring in 3C-SiC/zb-GaN by the Si and C atoms in the abrupt C–Ga, Si–Ga and Si–N, C–N interfaces, respectively, induce charge compensation and stabilize these interfaces. On the contrary, a mutual exchange of these two compensating atoms destroys the energetical stability of the discussed interfaces. Reconstruction of the C–N interface type, common for 3C-SiC/zb-GaN and diamond/c-BN by C atom, is energetically favourable in both heterostructures and it is accompanied by a similar charge transfer in [1 1 1], while the reconstruction of the analogous C–Ga and C–B interfaces is unfavourable in both cases. Finally, it is demonstrated that in the diamond/c-BN junctions grown along the [0 0 1] crystallographic direction, the most stable interfaces are of the C–N type with reconstruction in the uppermost substrate carbon layer.